The impact of Asian financial crisis toward Malaysian economy / Nurul Athira Misron and Wan Fatimah Az-Zahara Wan Mazlan - Misron, Nurul Athira; Wan Mazlan, Wan Fatimah Az-Zahara (2014)
The aim of this study is to investigate the impacts of Asian Financial Crisis towards Malaysian Economy. The study used Multiple Linear Regression in order to find the relationship among those variables. The yearly closing price of the data is collected from 1997 until 2007. It is conducted using 10 years period in order to get a reliable result. From the result, it reveals that only one variable have a significant relationship towards Malaysian economy. It means that there only a small relationships among this variables. These results further our understanding of the impacts of Asian Financial Crisis towards Malaysian economy should be useful for regulator, investor and speculator.